2021
DOI: 10.14808/sci.plena.2021.010201
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and potassium fertilization on cabbage biometrics and foliar nutritional levels

Abstract: Among the most absorbed nutrients by cabbage, nitrogen (N) and potassium (K) are the most extracted; thus, the objective of this study was to evaluate the responses of N and K fertilization on the cabbage biometrics and foliar levels of macro and micronutrients. Four N doses (0, 75, 150, 300 kg ha -1 of N) and four K doses (0, 75, 150, 300 kg ha -1 of K2O). Biometrics of cabbage head (height, circumference and diameter) and productivity were evaluated. The cabbage levels of macro and micronutrients were also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…In case of available soil potassium, combined effect of different doses of treatments resulted in higher level of soil potassium which might have increased the quantity of potassium in the soil, respectively. Similar positive results were also observed by Silva et al [18].…”
Section: Shelf Lifesupporting
confidence: 91%
See 1 more Smart Citation
“…In case of available soil potassium, combined effect of different doses of treatments resulted in higher level of soil potassium which might have increased the quantity of potassium in the soil, respectively. Similar positive results were also observed by Silva et al [18].…”
Section: Shelf Lifesupporting
confidence: 91%
“…This might be as a result of the soil receiving more potassium and the bacteria making it readily available to the plant. Silva et al [18] also observed rise in N and K content due to the combined effect of various fertilizer doses.…”
Section: Npk Content In Leaf (%)mentioning
confidence: 89%
“…Analyses on cabbage conducted by Nath [6] and Sumanth [7] confirm this conclusion. Also similar results were observed by Chamuah et al, [8] and Silva et al, [9] in cabbage.…”
Section: Plant Spread (Cm)supporting
confidence: 89%